Homefront - Gwaltney, Doris (New York : Simon & Schuster Books for Young Readers, 2006)
When her British aunt and cousin flee London during World War II and come to live in her family's farmhouse in Virginia, Margaret Ann is unhappy with having to share a room and having her life disrupted by a relative she hardly knows.
680
Accelerated Reader AR
Keywords: Cousins -- Fiction; World War, 1939-1945 -- Virginia -- Fiction; Family life -- Virginia -- Fiction; Farm life -- Virginia -- Fiction; Schools -- Fiction; Historical fiction